Data dissemination and query in mobile social networks - Jiming, Chen , 1978-; Jialu, Fan; Sun, Youxian (SpringerBriefs in computer science, 2012)
Presenting research topics, such as, MSNets as realistic social contact traces and user mobility models, this book includes the fundamental concepts of MSNets introduced including the background, key features and potential applications of MSNets